A comparative analysis of cryptocurrency wallet management tools - Biernacki, Kamil; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2021)
The work is devoted to a comparative analysis of tools for managing a cryptocurrency portfolio. The study aimed to find out which of the tools is currently the best solution for users. This analysis was carried out on the basis of two tools, first: a survey conducted of among 41 responders who are cryptocurrency users, and the second one: cognitive walkthrough. Conducted analysis confirmed the thesis that the Trust Wallet tool is currently the best solution for users.